Polymer Compositions for Electric Vehicles - Patent application

JP2025506386APending Publication Date: 2025-03-11TICONA LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024545941
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-14
Filing Date
2023-01-27
Publication Date
2025-03-11

Smart Images

  • Figure 2025506386000001_ABST
    Figure 2025506386000001_ABST
Patent Text Reader

Abstract

Disclosed is a polymer composition comprising a polyarylene sulfide, which can be utilized in forming components of an electric vehicle, such as electrical components and / or thermal management system components.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001]

[0001] This application is based on and claims priority to U.S. Provisional Patent Application No. 63 / 361,948, filed February 1, 2022, and U.S. Provisional Patent Application No. 63 / 309,695, filed February 14, 2022, which are incorporated by reference herein. [Background technology]

[0002]

[0002] Electric vehicles, such as battery electric vehicles, plug-in hybrid electric vehicles, mild hybrid electric vehicles, or full hybrid electric vehicles, generally have an electric powertrain including an electric propulsion source (e.g., a battery) and a transmission. Plastic materials are often used in electric vehicles for various components, such as high-voltage connectors, power conversion housings, battery assembly housings, fluid pumps, inverters, bus bars, twisted cables, individual sense leads, wire crimps, grommet moldings, quick connectors, tees, interconnects, guide rails, sealing rings (e.g., brushless DC sealing rings, battery cell sealing rings, etc.). Unfortunately, plastic materials often used for such components exhibit unsatisfactory mechanical properties (e.g., tensile strength and impact resistance) for successful long-term use in the harsh environments that will be encountered in electric vehicles. Moreover, many plastic materials exhibit processing properties (e.g., melt viscosity, molding properties) that make it difficult to mold final products, such as electric vehicle components, with high product losses, especially for moldings with strict tolerance requirements. Thus, there is currently a need for polymer compositions that exhibit desirable mechanical and processing properties for advantageous use in a wide variety of applications, particularly in electric vehicle components. Summary of the Invention [Means for solving the problem]

[0003]

[0003] According to one embodiment of the present invention, a polymer composition is disclosed comprising 100 parts by weight of at least one polyarylene sulfide, about 10 to about 80 parts by weight of a fibrous filler, about 1 to about 20 parts by weight of at least one impact modifier, and about 0.1 to about 10 parts by weight of an ultra-high molecular weight siloxane polymer having a weight average molecular weight of about 100,000 grams / mole or more.

[0004]

[0004] Other features and aspects of the present invention are described in more detail below.

[0005] A full and enabling disclosure of the present invention, including the best mode thereof, to one skilled in the art, is set forth more particularly in the remainder of the specification, including reference to the accompanying drawings, in which: [Brief description of the drawings]

[0005] [Figure 1]

[0006] 1 illustrates an electric vehicle that includes components into which the polymer compositions disclosed herein can be incorporated. [Diagram 2]

[0007] 1 illustrates one embodiment of a busbar that can incorporate the polymer composition disclosed herein. [Diagram 3]

[0008] 1 illustrates a battery assembly that may employ components into which the polymer compositions disclosed herein may be incorporated. [Figure 4]

[0009] 1 illustrates an electronic system that may include components into which the polymer compositions disclosed herein may be incorporated. [Diagram 5]

[0010] 5 illustrates a current sensor that may be included in the electronic system of FIG. 4. [Figure 6]

[0011] 1 illustrates an inverter system that may be present in an electric vehicle that includes components into which the polymer compositions disclosed herein may be incorporated. [Figure 7]

[0012] FIG. 1 is a perspective view of one embodiment of a connector into which the polymer compositions disclosed herein can be incorporated. [Figure 8]

[0013] 8 is a top view of the connector of FIG. 7, with the first connector portion and the second connector portion separated. [Figure 9]

[0014] 8 is a plan view of the connector of FIG. 7, with the first connector portion and the second connector portion mated; FIG. [Figure 10]

[0015] Illustrated are examples of components into which the polymer compositions disclosed herein can be incorporated. [Figure 11]

[0016] 1 illustrates additional components into which the polymer compositions disclosed herein may be incorporated. [Figure 12]

[0017] 1 illustrates a low temperature thermal loop that may include components into which the polymer compositions disclosed herein may be incorporated. [Figure 13]

[0018] 1 illustrates a high temperature thermal loop that may include components into which the polymer compositions disclosed herein may be introduced. [Figure 14]

[0019] 1 illustrates one embodiment of a water pump into which the polymer compositions disclosed herein can be incorporated. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0006]

[0020] Repeat use of reference characters in the present specification and drawings is intended to represent same or analogous features or elements of the invention.

[0021] Those skilled in the art will appreciate that this discussion is a description of exemplary embodiments only and is not intended to limit the broader aspects of the invention.

[0007]

[0022] Generally speaking, the present invention is directed to polymer compositions that exhibit desirable processing and mechanical properties for use in components of electric vehicles, such as battery powered electric vehicles, fuel cell vehicles, plug-in hybrid electric vehicles (PHEVs), mild hybrid electric vehicles (MHEVs), and full hybrid electric vehicles (FHEVs).

[0008]

[0023] The polymer composition may be, for example, subjected to a temperature of about 310° C. and a shear rate of 400 s in accordance with ISO 11443:2021. -1 In some embodiments, the polymer composition may exhibit a relatively low melt viscosity, such as about 30 kP or less, in some embodiments about 20 kP or less, in some embodiments about 10 kP or less, in some embodiments about 5 kP or less, and in some embodiments about 2 to about 50 kP, as determined according to ISO 180:2019. Despite having a low melt viscosity, the polymer composition may still maintain high impact and tensile strength, and may provide enhanced flexibility to the resulting component. For example, the polymer composition may have a melt viscosity of about 5 kJ / m2 as determined according to ISO 180:2019 at a temperature of 23° C. 2 or more, for example, in some embodiments, from about 6 to about 50 kJ / m 2 In some embodiments, from about 7 to about 30 kJ / m 2 and a notched Izod impact strength of about 6 kJ / m, as determined at 23° C. according to ISO 179-1:2010. 2 or more, for example, in some embodiments, from about 8 to about 50 kJ / m 2 In some embodiments, from about 10 to about 30 kJ / m 2 For example, the composition may exhibit a tensile stress at break of about 100 MPa or more, and in some embodiments, from about 100 MPa to about 200 MPa, and in some embodiments, from about 110 to about 180 MPa, and in some embodiments, from about 120 to about 170 MPa; a tensile strain at break of about 1% or more, and in some embodiments, from about 1% to about 10%; and / or a tensile modulus of about 15,000 MPa or less, and in some embodiments, from about 1,000 MPa to about 12,000 MPa, and in some embodiments, from about 5,000 MPa to about 11,000 MPa. Tensile properties may be determined at a temperature of 23° C. according to ISO Test No. 527:2019.

[0009]

[0024] Notably, however, the inventors have also discovered that the polymer composition is not highly sensitive to aging at elevated temperatures. For example, a part formed from the composition may be aged in an atmosphere having a temperature of about 100° C. or higher, in some embodiments about 150° C. to about 200° C., in some embodiments about 200° C. to about 260° C. (e.g., 240° C.) for a period of about 100 hours or more, in some embodiments about 300 hours to about 3000 hours, in some embodiments about 400 hours to about 2500 hours (e.g., about 1,000 hours). Even after aging, the mechanical properties (e.g., impact strength, tensile properties, and / or flexural properties) may remain within the above ranges. For example, the ratio of a particular mechanical property (e.g., unnotched Charpy impact strength, tensile modulus, tensile strength, tensile strain at break, etc.) after 1000 hours of "aging" at 240° C. to the initial mechanical property before the aging may be about 0.4 or more, in some embodiments about 0.5 or more, and in some embodiments about 0.6 to 1.0. In one embodiment, for example, the notched Charpy impact strength of the part is about 5 kJ / m when measured at a temperature of 23° C. according to ISO 179-1:2010 after aging at elevated temperature (e.g., 240° C.) for 1,000 hours. 2 and in some embodiments, from about 6 to about 30 kJ / m 2 In some embodiments, from about 7 to about 20 kJ / m 2 After aging at an elevated temperature atmosphere (e.g., 240° C.) for 1,000 hours, the part may also exhibit a tensile strength of about 50 to about 300 MPa, and in some embodiments about 80 to about 200 MPa, and in some embodiments about 100 to about 150 MPa; a tensile modulus of about 5,000 to about 25,000 MPa, and in some embodiments about 8,000 to about 22,000 MPa, and in some embodiments about 10,000 to about 20,000 MPa; and / or a tensile strain at break of about 0.4% to about 8%, and in some embodiments about 0.6% to about 5%, and in some embodiments about 0.8% to about 3%, as determined at a temperature of 23° C. according to ISO 527-2 / 1A:2019.

[0010]

[0025] The polymer composition may also exhibit good heat resistance and flame retardant properties. As an example, the polymer composition may meet the V-0 flammability standard at a thickness of 0.2 millimeters. Flame retardant efficacy may be determined according to the UL94 vertical flame test procedure in "Test for Flammability of Plastic Materials for Parts in Devices and Appliances", 5th Edition, October 29, 1996. The UL94 test ratings are listed in the table below:

[0011] [Table 1]

[0012]

[0026] "Afterflame time" is an average value determined by dividing the total afterflame time (sum of all samples tested) by the number of samples. The total afterflame time is the sum of the time (in seconds) that all samples remain ignited after two separate applications of flame as described in the UL94 VTM test. A shorter time indicates better flame resistance, i.e., the flame is extinguished faster. For a V-0 rating, the total afterflame time of five samples, each with two applications of flame, must be within 50 seconds. Using the flame retardant of the present invention, the polymer composition can achieve at least a V-1 rating, and typically a V-0 rating, for a 0.8 millimeter thick specimen.

[0013]

[0027] Various embodiments of the invention will now be described in greater detail below. I. Polymer Composition A. Polyarylene sulfide

[0028] The polyarylene sulfide typically comprises from about 50 wt% to about 98 wt%, in some embodiments from about 55 wt% to about 95 wt%, and in some embodiments from about 60 wt% to about 90 wt% of the polymer composition. The polyarylene sulfide used in the composition generally has repeating units of the formula: -[(Ar 1 ) n -X] m -[(Ar2 ) i -Y] j -[(Ar 3 ) k -Z] l -[(Ar 4 ) o -W] p - (In the formula, Ar 1 , Ar 2 , Ar 3 , and Ar 4 are independently arylene units of 6 to 18 carbon atoms; W, X, Y, and Z are independently divalent linking groups selected from -SO2-, -S-, -SO-, -CO-, -O-, -C(O)O-, or alkylene or alkylidene groups of 1 to 6 carbon atoms, where at least one of the linking groups is -S-; n, m, i, j, k, l, o, and p are independently 0, 1, 2, 3, or 4, provided that the sum thereof is greater than or equal to 2.

[0014]

[0029] Arylene unit Ar 1 , Ar 2 , Ar 3 , and Ar 4 may be optionally substituted or unsubstituted. Advantageous arylene units are phenylene, biphenylene, naphthalene, anthracene and phenanthrene. Polyarylene sulfides typically contain more than about 30 mol%, more than about 50 mol%, or more than about 70 mol% of arylene sulfide (-S-) units. For example, polyarylene sulfides may contain at least 85 mol% of sulfide bonds directly bonded to two aromatic rings. In a particular embodiment, polyarylene sulfides contain as their components the phenylene sulfide structure -(C6H4-S) n - (wherein n is an integer equal to or greater than 1).

[0015]

[0030] The synthesis techniques that can be used to make polyarylene sulfide are generally known in the art. For example, the process for producing polyarylene sulfide may include reacting a substance that produces hydrosulfide ions (e.g., an alkali metal sulfide) with a dihaloaromatic compound in an organic amide solvent. The alkali metal sulfide may be, for example, lithium sulfide, sodium sulfide, potassium sulfide, rubidium sulfide, cesium sulfide, or a mixture thereof. If the alkali metal sulfide is a hydrate or an aqueous mixture, it may be treated by a dehydration process prior to the polymerization reaction. The alkali metal sulfide may also be generated in situ. In addition, a small amount of alkali metal hydroxide may be included in the reaction to remove or react impurities such as alkali metal polysulfides or alkali metal thiosulfates that may be present in very small amounts together with the alkali metal sulfide (to convert the impurities into harmless substances).

[0016]

[0031] The dihaloaromatic compound may be, but is not limited to, o-dihalobenzene, m-dihalobenzene, p-dihalobenzene, dihalotoluene, dihalonaphthalene, methoxy-dihalobenzene, dihalobiphenyl, dihalobenzoic acid, dihalodiphenyl ether, dihalodiphenyl sulfone, dihalodiphenyl sulfoxide or dihalodiphenyl ketone. The dihaloaromatic compound may be used alone or in any combination thereof. Specific exemplary dihaloaromatic compounds include, but are not limited to, p-dichlorobenzene, m-dichlorobenzene, O-dichlorobenzene, 2,5-dichlorotoluene, 1,4-dibromobenzene, 1,4-dichloronaphthalene, 1-methoxy-2,5-dichlorobenzene, 4,4'-dichlorobiphenyl, 3,5-dichlorobenzoic acid, 4,4'-dichlorodiphenyl ether, 4,4'-dichlorodiphenyl sulfone, 4,4'-dichlorodiphenyl sulfoxide, and 4,4'-dichlorodiphenyl ketone. The halogen atom may be fluorine, chlorine, bromine, or iodine, and the two halogen atoms in the same dihaloaromatic compound may be the same or different from each other. In one embodiment, O-dichlorobenzene, m-dichlorobenzene, p-dichlorobenzene, or a mixture of two or more of these compounds is used as the dihaloaromatic compound. As is known in the art, it is also possible to use a monohalo compound (not necessarily an aromatic compound) in combination with a dihaloaromatic compound to form an end group of the polyarylene sulfide or to adjust the polymerization reaction and / or the molecular weight of the polyarylene sulfide.

[0017]

[0032] Polyarylene sulfides may be homopolymers or copolymers. For example, the selective combination of dihaloaromatic compounds can produce polyarylene sulfide copolymers containing two or more different units. For example, when p-dichlorobenzene is used in combination with m-dichlorobenzene or 4,4'-dichlorodiphenyl sulfone, the following formula is obtained:

[0018] [ka]

[0019] and a segment having the structure:

[0020] [ka]

[0021] or a segment having the structure:

[0022] [ka]

[0023] Polyarylene sulfide copolymers can be formed which contain segments having the structure:

[0033] Polyarylene sulfide may be linear, semi-linear, branched or crosslinked. Linear polyarylene sulfide typically contains 80 mol% or more of the repeat unit -(Ar-S)-. Such linear polymers may also contain a small amount of branched or crosslinked units, but the amount of branched or crosslinked units is typically less than about 1 mol% of the total monomer units of the polyarylene sulfide. Linear polyarylene sulfide polymers may be random or block copolymers containing the repeat units described above. Semi-linear polyarylene sulfide may also have a crosslinked or branched structure introduced into the polymer in small amounts of one or more monomers having three or more reactive functional groups. As an example, the monomer components used in forming semi-linear polyarylene sulfide include to some extent polyhaloaromatic compounds having two or more halogen substituents per molecule that can be utilized in preparing branched polymers. Such monomers are represented by the formula R'X nwhere each X is selected from chlorine, bromine, and iodine, n is an integer from 3 to 6, and R' is a polyvalent aromatic group of valence n that may have up to about four methyl substituents, and the total number of carbon atoms in R' is in the range of 6 to about 16. Examples of some polyhaloaromatic compounds substituted with more than two halogens per molecule that can be used to form semi-linear polyarylene sulfides include 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, 1,3-dichloro-5-bromobenzene, 1,2,4-triiodobenzene, 1,2,3,5-tetrabromobenzene, hexachlorobenzene, 1,3,5-trichloro-2,4,6-trimethylbenzene, 2,2',4,4'-tetrachlorobiphenyl, 2,2',5,5'-tetra-iodobiphenyl, 2,2',6,6'-tetrabromo-3,3',5,5'-tetramethylbiphenyl, 1,2,3,4-tetrachloronaphthalene, 1,2,4-tribromo-6-methylnaphthalene, and the like, and mixtures thereof.

[0024]

[0034] If desired, the polyarylene sulfide can be functionalized. For example, a disulfide compound containing reactive functional groups (e.g., carboxyl, hydroxyl, amine, etc.) can react with the polyarylene sulfide. In addition, functionalization of the polyarylene sulfide can provide binding sites between any optional impact modifier and the polyarylene sulfide, which can improve the distribution of the impact modifier throughout the polyarylene sulfide to prevent phase separation. The disulfide compound can undergo a chain scission reaction with the polyarylene sulfide during melt processing to reduce the overall melt viscosity. When used, the disulfide compound typically comprises about 0.01 wt% to about 3 wt%, in some embodiments about 0.02 wt% to about 1 wt%, and in some embodiments about 0.05 to about 0.5 wt% of the polymer composition. The ratio of the amount of polyarylene sulfide to the amount of disulfide compound may also be from about 1000:1 to about 10:1, from about 500:1 to about 20:1, or from about 400:1 to about 30:1. Suitable disulfide compounds are typically those having the formula: R 3 -SSR 4

[0035] In the formula, R 3 and R 4 are the same or different and are independently a hydrocarbon group containing 1 to about 20 carbon atoms. For example, R 3 and R 4 may be an alkyl, cycloalkyl, aryl, or heterocyclic group. In certain embodiments, R 3 and R 4 R is generally a non-reactive functional group, such as phenyl, naphthyl, ethyl, methyl, propyl, etc. Examples of such compounds include diphenyl disulfide, naphthyl disulfide, dimethyl disulfide, diethyl disulfide, and dipropyl disulfide. 3 and R 4 may also contain reactive functional groups at the end groups of the disulfide compound. For example, R 3 and R 4At least one of the may include a terminal carboxyl group, a hydroxyl group, a substituted or unsubstituted amino group, or a nitro group, etc. Exemplary compounds may include, but are not limited to, 2,2'-diaminodiphenyl disulfide, 3,3'-diaminodiphenyl disulfide, 4,4'-diaminodiphenyl disulfide, dibenzyl disulfide, dithiosalicylic acid (or 2,2'-dithiobenzoic acid), dithioglycolic acid, α,α'-dithiodilactic acid, β,β'-dithiodilactic acid, 3,3'-dithiodipyridine, 4,4'-dithiomorpholine, 2,2'-dithiobis(benzothiazole), 2,2'-dithiobis(benzimidazole), 2,2'-dithiobis(benzoxazole), 2-(4'-morpholinodithio)benzothiazole, and the like, and mixtures thereof.

[0025]

[0036] The melt flow rate of the polyarylene sulfide incorporated in the composition, as determined according to ISO 1133 at a load of 5 kg and a temperature of 316° C., may be from about 100 to about 800 grams per 10 minutes ("g / 10 min"), in some embodiments from about 200 to about 700 g / 10 min, and in some embodiments from about 300 to about 600 g / 10 min.

[0026] B. Impact Modifiers

[0037] As indicated above, impact modifiers are also used in the polymer composition. Typically, the impact modifier comprises about 1 to about 20 parts by weight, in some embodiments about 2 to about 15 parts by weight, and in some embodiments about 5 to about 10 parts by weight, per 100 parts by weight of polyarylene sulfide. For example, the impact modifier may comprise about 0.1 wt% to about 20 wt%, in some embodiments about 0.5 wt% to about 15 wt%, and in some embodiments about 1 wt% to about 10 wt% of the polymer composition.

[0027]

[0038] Examples of suitable impact modifiers include, for example, polyepoxides, polyurethanes, polybutadienes, acrylonitrile-butadiene-styrenes, polyamides, block copolymers (e.g., polyether-polyamide block copolymers), and the like, and mixtures thereof. In one embodiment, an "epoxy-functionalized" olefin copolymer is used, which contains an average of two or more epoxy functional groups per molecule. The copolymer generally contains olefinic monomer units derived from one or more α-olefins. Examples of such monomers include, for example, linear and / or branched α-olefins having 2 to 20 carbon atoms, typically 2 to 8 carbon atoms. Specific examples include ethylene, propylene, 1-butene; 3-methyl-1-butene; 3,3-dimethyl-1-butene; 1-pentene; 1-pentene with one or more methyl, ethyl or propyl substituents; 1-hexene with one or more methyl, ethyl or propyl substituents; 1-heptene with one or more methyl, ethyl or propyl substituents; 1-octene with one or more methyl, ethyl or propyl substituents; 1-nonene with one or more methyl, ethyl or propyl substituents; ethyl, methyl or dimethyl substituted 1-decene; 1-dodecene, and styrene. Particularly desirable α-olefin monomers are ethylene and propylene. The copolymer may also contain epoxy-functional monomer units. One example of such a unit is an epoxy-functional (meth)acrylic monomer component. As used herein, the term "(meth)acrylic" includes acrylic and methacrylic monomers, as well as their salts or esters, such as acrylate and methacrylate monomers. For example, suitable epoxy-functional (meth)acrylic monomers can include, but are not limited to, those containing 1,2-epoxy groups, such as glycidyl acrylate and glycidyl methacrylate. Other suitable epoxy-functional monomers include allyl glycidyl ether, glycidyl ethacrylate, and glycidyl itaconate.Other suitable monomers may also be used to help achieve the desired molecular weight.

[0028]

[0039] Of course, the copolymer may also contain other monomer units known in the art. For example, another suitable monomer may include a non-epoxy-functional (meth)acrylic monomer. Examples of such (meth)acrylic monomers include methyl acrylate, ethyl acrylate, n-propyl acrylate, i-propyl acrylate, n-butyl acrylate, s-butyl acrylate, i-butyl acrylate, t-butyl acrylate, n-amyl acrylate, i-amyl acrylate, isobornyl acrylate, n-hexyl acrylate, 2-ethylbutyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, n-decyl acrylate, methylcyclohexyl acrylate, cyclopentyl acrylate, cyclohexyl acrylate, methyl methacrylate, ethyl ... Examples of the copolymer include methyl, 2-hydroxyethyl methacrylate, n-propyl methacrylate, n-butyl methacrylate, i-propyl methacrylate, i-butyl methacrylate, n-amyl methacrylate, n-hexyl methacrylate, i-amyl methacrylate, s-butyl methacrylate, t-butyl methacrylate, 2-ethylbutyl methacrylate, methylcyclohexyl methacrylate, cinnamyl methacrylate, crotyl methacrylate, cyclohexyl methacrylate, cyclopentyl methacrylate, 2-ethoxyethyl methacrylate, isobornyl methacrylate, and the like, and combinations thereof. In a particular embodiment, for example, the copolymer may be a terpolymer formed from an epoxy-functional (meth)acrylic monomer component, an α-olefin monomer component, and a non-epoxy-functional (meth)acrylic monomer component. The copolymer may have, for example, the following structure:

[0029] [ka]

[0030] (wherein x, y, and z are 1 or greater). The copolymer may be poly(ethylene-co-butyl acrylate-co-glycidyl methacrylate) having the formula:

[0031]

[0040] The relative proportions of the monomeric components may be selected to achieve a balance between epoxy reactivity and melt flow rate. More specifically, a high epoxy monomer content may provide good reactivity with the polyarylene sulfide, but too much content may reduce the melt flow rate to such an extent that the copolymer adversely affects the melt strength of the polymer blend. Thus, in most embodiments, the epoxy-functional (meth)acrylic monomer comprises from about 1 wt% to about 20 wt%, in some embodiments from about 2 wt% to about 15 wt%, and in some embodiments from about 3 wt% to about 10 wt% of the copolymer. The α-olefin monomer may likewise comprise from about 55 wt% to about 95 wt%, in some embodiments from about 60 wt% to about 90 wt%, and in some embodiments from about 65 wt% to about 85 wt% of the copolymer. Other monomeric components (e.g., non-epoxy functional (meth)acrylic monomers), if used, may comprise from about 5 wt% to about 35 wt%, in some embodiments from about 8 wt% to about 30 wt%, and in some embodiments from about 10 wt% to about 25 wt% of the copolymer. The resulting melt flow rates, as determined according to ASTM D1238-13 at a load of 2.16 kg and a temperature of 190° C., are typically from about 1 to about 30 grams per 10 minutes ("g / 10 min"), in some embodiments from about 2 to about 20 g / 10 min, and in some embodiments from about 3 to about 15 g / 10 min.

[0032]

[0041] Additional impact modifiers may also be used in combination with the epoxy-functional impact modifier if desired. For example, the additional impact modifier may include a block copolymer in which at least one phase is made of a material that is hard at room temperature but becomes fluid when heated, and the other phase is a soft material such as rubber at room temperature. By way of example, the block copolymer may have an AB or ABA block copolymer repeat structure, where A represents the hard segment and B is the soft segment. Non-limiting examples of impact modifiers with an AB repeat structure include polyamide / polyether, polysulfone / polydimethylsiloxane, polyurethane / polyester, polyurethane / polyether, polyester / polyether, polycarbonate / polydimethylsiloxane, and polycarbonate / polyether. Triblock copolymers may also contain polystyrene as the hard segment and either polybutadiene, polyisoprene, or polyethylene-co-butylene as the soft segment. Styrene-butadiene repeat copolymers and polystyrene / polyisoprene repeat polymers may also be used. In a particular embodiment, the block copolymer may have alternating blocks of polyamide and polyether. Such materials are commercially available, for example, from Atofina under the trade name PEBAX™. The polyamide blocks may be derived from copolymers of diacid and diamine components, or may be prepared by homopolymerization of cyclic lactams. The polyether blocks may be derived from homo- or copolymers of cyclic ethers such as ethylene oxide, propylene oxide, and tetrahydrofuran.

[0033] C. Siloxane Polymers

[0042] Siloxane polymers are also used in the polymer composition. The siloxane polymer typically comprises about 0.05 to about 10 parts by weight, in some embodiments about 0.1 to about 8 parts by weight, and in some embodiments about 0.5 to about 5 parts by weight, per 100 parts by weight of polyarylene sulfide. For example, the siloxane polymer may comprise about 0.05 wt% to about 15 wt%, in some embodiments about 0.5 wt% to about 10 wt%, and in some embodiments about 1 wt% to about 8 wt% of the polymer composition.

[0034]

[0043] Without intending to be limited by theory, it is believed that the siloxane polymer can improve the processing of the composition, for example, by providing better mold filling, internal lubrication, demolding, etc., among others. In addition, it is also believed that the siloxane polymer is less likely to migrate or diffuse to the surface of the composition, which further minimizes the possibility of phase separation and further aids in reducing impact energy. The siloxane polymer has a high molecular weight, for example, about 100,000 grams / mole or more, in some embodiments, about 200,000 grams / mole or more, and in some embodiments, about 500,000 grams / mole to about 2,000,000 grams / mole. The siloxane polymer has a relatively high dynamic viscosity at 25° C., for example, about 10,000 centistokes or more, in some embodiments, about 30,000 centistokes or more, and in some embodiments, about 50,000 to about 50×10 6 Centistokes, e.g., about 1 x 10 6 ~50×10 6 The viscosity of the siloxane polymer can be determined according to ASTM D445-21.

[0035]

[0044] Any of a variety of high molecular weight siloxane polymers can generally be used in the polymer composition. High molecular weight siloxane polymers generally contain siloxane-based monomer residue repeat units. As used herein, "siloxane" refers to a polymer having the following structure:

[0036] [ka]

[0037] (In the formula, R 1 and R 2 are independently hydrogen or a hydrocarbyl moiety, known in silicone chemistry as the "M" group. The repeating monomeric residue unit has the formula:

[0038]

[0045] Silicones are known as the "Q" group in silicone chemistry

[0039] [ka]

[0040] or known in silicone chemistry as the "T" group

[0041] [ka]

[0042] It may also include branch points such as

[0046] As used herein, the term "hydrocarbyl" refers to a monovalent group formed by removing a hydrogen atom from a hydrocarbon (e.g., an alkyl group such as ethyl, or an aryl group such as phenyl). In one or more embodiments, the siloxane monomer residue may be either a dialkyl, diaryl, dialkaryl, or diaralkyl siloxane having the same or different alkyl, aryl, alkaryl, or aralkyl moieties. In one embodiment, R 1 and R 2 Each of C1 to C 20 , C1~C 12or C1-C6 alkyl (e.g., methyl, ethyl, propyl, butyl, etc.), aryl (e.g., phenyl), alkaryl, aralkyl, cycloalkyl (e.g., cyclopentyl), arylenyl, alkenyl, cycloalkenyl (e.g., cyclohexenyl), alkoxy (e.g., methoxy), etc., and combinations thereof. In various embodiments, R 1 and R 2 may have the same or different number of carbon atoms. In various embodiments, R 1 and R 2 Each hydrocarbyl group in is a saturated and optionally linear alkyl group. In addition, the alkyl group in such an embodiment is a saturated and optionally linear alkyl group in the polymer chain. 1 and R 2 can be identical for each of R 1 and R 2 Non-limiting examples of alkyl groups suitable for use in include methyl, ethyl, 1-propyl, 2-propyl, 1-butyl, isobutyl, t-butyl, or combinations of two or more thereof.

[0043]

[0047] Additionally, the siloxane polymer may contain R groups such as vinyl groups, hydroxyl groups, hydrides, isocyanate groups, epoxy groups, acid groups, halogen atoms, alkoxy groups, acyloxy groups, ketoximate groups, amino groups, amide groups, acid amide groups, aminooxy groups, mercapto groups, alkenyloxy groups, alkoxyalkoxy groups, or aminoxy groups and combinations thereof. 1 and / or R 2 The siloxane polymer may contain a variety of end groups as groups. Additionally, the polymer composition may contain a mixture of two or more siloxane polymers.

[0044]

[0048] In some embodiments, high molecular weight siloxane polymers can be demonstrated by copolymerizing a plurality of siloxane polymers having low weight average molecular weights (e.g., molecular weights less than 100,000 grams / mole) with a polysiloxane linker. In one particular embodiment, by way of example, a resin can be formed by copolymerizing one or more low molecular weight siloxane polymers with a linear polydiorganosiloxane linker as described in U.S. Patent No. 6,072,012 (Juen et al.). The substantially linear polydiorganosiloxane linker can be of the general formula: (R 3 (3-p) R 4 p SiO 1 / 2 )(R 3 2SiO 2 / 2 ) x ((R 3 R 4 SiO 2 / 2 )(R 3 2SiO 2 / 2 ) x ) y (R 3 (3-p) R 4 p SiO 1 / 2 ) [In the formula, Each R 3 is independently a monovalent radical selected from the group consisting of alkyl, aryl, and arylalkyl groups; Each R 4 are independently monovalent radicals selected from the group consisting of hydrogen, hydroxyl, alkoxy, oximo, alkyloximo, and aryloximo groups, where at least two R 5 The groups are typically present in each molecule and attached to different silicon atoms; p is 0, 1, 2, or 3; x ranges from 0 to 200, and in some embodiments, from 0 to 100; y ranges from 0 to 200, and in some embodiments, from 0 to 100. may have.

[0045]

[0049] In certain embodiments, the siloxane polymer may be provided in the form of a masterbatch that includes a carrier resin. The carrier resin may, for example, comprise from about 0.05 wt% to about 15 wt%, in some embodiments from about 0.1 wt% to about 10 wt%, and in some embodiments, from about 0.5 wt% to about 8 wt% of the polymer composition. Any of a variety of carrier resins may be used, such as polyolefins (e.g., ethylene polymers, propylene polymers, etc.), polyamides, etc. In one embodiment, for example, the carrier resin is an ethylene polymer. Ethylene polymers are polymers that are made up of ethylene and C3-C6 20 α-Olefin or C3-C 12 They may also be copolymers with α-olefins such as α-olefins. Suitable α-olefins may be linear or branched (e.g., one or more C1-C3 alkyl branches, or aryl groups). Specific examples include 1-butene; 3-methyl-1-butene; 3,3-dimethyl-1-butene; 1-pentene; 1-pentene with one or more methyl, ethyl, or propyl substituents; 1-hexene with one or more methyl, ethyl, or propyl substituents; 1-heptene with one or more methyl, ethyl, or propyl substituents; 1-octene with one or more methyl, ethyl, or propyl substituents; 1-nonene with one or more methyl, ethyl, or propyl substituents; ethyl, methyl, or dimethyl substituted 1-decene; 1-dodecene; and styrene. Particularly desirable α-olefin comonomers are 1-butene, 1-hexene, and 1-octene. The ethylene content of such copolymers may be from 60 mol % to about 99 mol %, in some embodiments from about 80 mol % to about 98.5 mol %, and in some embodiments, from about 87 mol % to about 97.5 mol %. The α-olefin content may similarly range from about 1 mol % to about 40 mol %, in some embodiments from about 1.5 mol % to about 15 mol %, and in some embodiments, from about 2.5 mol % to about 13 mol %. The density of ethylene polymers may vary depending on the type of polymer used, but is generally from about 0.85 to about 0.96 grams per cubic centimeter (g / cm 3 ). 3 ) range. Polyethylene "plastomer" is, for example, about 0.85 to about 0.91 g / cm 3Similarly, "linear low density polyethylene" (LLDPE) can have a density ranging from about 0.91 to about 0.940 g / cm, as determined according to ASTM D792. 3 and "low density polyethylene" (LDPE) can have a density ranging from about 0.910 to about 0.940 g / cm 3 and "high density polyethylene" (HDPE) may have a density ranging from about 0.940 to about 0.960 g / cm 3 Some non-limiting examples of high molecular weight siloxane polymer masterbatches that can be used include those available from Dow Corning under the trade names MB50-001, MB50-002, MB50-313, MB50-314, and MB50-321.

[0046] D. Fibrous fillers

[0050] Fibrous fillers are also used in the polymer composition. The fibrous fillers typically comprise about 10 to about 80 parts by weight, in some embodiments about 20 to about 75 parts by weight, and in some embodiments about 25 to about 60 parts by weight, per 100 parts by weight of polyarylene sulfide. For example, the fibrous fillers may comprise about 10 wt% to about 60 wt%, in some embodiments about 15 wt% to about 50 wt%, and in some embodiments about 20 wt% to about 45 wt% of the polymer composition.

[0047]

[0051] Any of a variety of different types of fibers can generally be used, such as glass; silicates such as neosilicates, sorosilicates, inosilicates (e.g., calcium inosilicates such as wollastonite; calcium magnesium inosilicates such as tremolite; calcium magnesium iron inosilicates such as anthracite; magnesium iron inosilicates such as anthophyllite; phyllosilicates (e.g., aluminum phyllosilicates such as palygorskite), tectosilicates, and the like; inorganic fibers derived from sulfates such as calcium sulfates (e.g., dehydrated or anhydrite); and mineral wool (e.g., rock or slag wool). Particularly suitable for use in the present invention are glass fibers such as those formed from E-glass, A-glass, C-glass, D-glass, AR-glass, R-glass, S1-glass, S2-glass, and the like, and mixtures thereof. If desired, the glass fibers can be provided with a size or other coatings known in the art.

[0048]

[0052] The fibers may have any desired cross-sectional shape, such as round, flat, etc. In certain embodiments, it may be desirable to use fibers having relatively flat cross-sectional dimensions by having an aspect ratio (i.e., cross-sectional width divided by cross-sectional thickness) of about 1.5 to about 10, in some embodiments about 2 to about 8, and in some embodiments about 3 to about 5. When such flat fibers are used in certain concentrations, the mechanical properties of the molded part may be further improved without substantially adversely affecting the melt viscosity of the polymer composition. The fibers may have a nominal width, for example, of about 1 to about 50 micrometers, in some embodiments about 5 to about 50 micrometers, and in some embodiments about 10 to about 35 micrometers. The fibers may also have a nominal thickness of about 0.5 to about 30 micrometers, in some embodiments about 1 to about 20 micrometers, and in some embodiments about 3 to about 15 micrometers. Additionally, the fibers may have a narrow size distribution. That is, at least about 60% by volume, and in some embodiments at least about 70% by volume, and in some embodiments at least about 80% by volume of the fibers may have a width and / or thickness within the above ranges. In the molded part, the fibers may have a volume average length of from about 10 to about 500 micrometers, and in some embodiments, from about 100 to about 400 micrometers, and in some embodiments, from about 150 to about 350 micrometers.

[0049] E. Other Ingredients

[0053] In addition to the above components, the polymer composition may also contain various other optional components to help improve overall properties. In one embodiment, for example, the organosilane compound may be used in the polymer composition in an amount of, for example, about 0.1 to about 8 parts by weight, in some embodiments about 0.3 to about 5 parts by weight, and in some embodiments about 0.5 to about 3 parts by weight, per 100 parts by weight of polyarylene sulfide. For example, the organosilane compound may comprise about 0.01 wt % to about 3 wt %, in some embodiments about 0.02 wt % to about 2 wt %, and in some embodiments about 0.05 to about 1 wt % of the polymer composition. The organosilane compound may be, for example, any alkoxysilane known in the art, such as vinylalkoxysilane, epoxyalkoxysilane, aminoalkoxysilane, mercaptoalkoxysilane, and combinations thereof. In one embodiment, for example, the organosilane compound may be represented by the following general formula: R 5 -Si-(R 6 )3 [In the formula, R 5 are sulfide groups (e.g., -SH), alkyl sulfides containing 1 to 10 carbon atoms (e.g., mercaptopropyl, mercaptoethyl, mercaptobutyl, etc.), alkenyl sulfides containing 2 to 10 carbon atoms, alkynyl sulfides containing 2 to 10 carbon atoms, amino groups (e.g., NH2), aminoalkyls containing 1 to 10 carbon atoms (e.g., aminomethyl, aminoethyl, aminopropyl, aminobutyl, etc.); aminoalkenyls containing 2 to 10 carbon atoms, and aminoalkynyls containing 2 to 10 carbon atoms; R 6 is an alkoxy group of 1 to 10 carbon atoms, such as methoxy, ethoxy, and propoxy. may have.

[0050]

[0054] Some representative examples of organosilane compounds that may be included in the mixture include mercaptopropyltrimethoxysilane, mercaptopropyltriethoxysilane, aminopropyltriethoxysilane, aminoethyltriethoxysilane, aminopropyltrimethoxysilane, aminoethyltrimethoxysilane, ethylenetrimethoxysilane, ethylenetriethoxysilane, ethynetrimethoxysilane, ethynetriethoxysilane, aminoethylaminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropylmethyldimethoxysilane or 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl) -3-aminopropyltrimethoxysilane, N-methyl-3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, bis(3-aminopropyl)tetramethoxysilane, bis(3-aminopropyl)tetraethoxydisiloxane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, γ-diallylaminopropyltrimethoxysilane, γ-diallylaminopropyltrimethoxysilane, and the like, and combinations thereof. Particularly suitable organosilane compounds are 3-aminopropyltriethoxysilane and 3-mercaptopropyltrimethoxysilane.

[0051]

[0055] The polymer composition may also contain a heat stabilizer. By way of example, the heat stabilizer may be a phosphite stabilizer, such as an organic phosphite. For example, suitable phosphite stabilizers include monophosphites and diphosphites, where diphosphites have a molecular structure that inhibits moisture absorption and / or has a relatively high spiro isomer content. By way of example, a diphosphite stabilizer having a spiro isomer content of greater than 90%, such as greater than 95%, such as greater than 98%, may be selected. Specific examples of such diphosphite stabilizers include, for example, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, bis(2,4-di-t-butylphenyl)pentaerythritol diphosphite, distearyl pentaerythritol diphosphite, mixtures thereof, and the like. When used, the heat stabilizer typically comprises from about 0.1 wt% to about 3 wt%, and in some embodiments, from about 0.2 wt% to about 2 wt% of the composition.

[0052]

[0056] Nucleating agents can also be used to further enhance the crystallization properties of the composition. One example of such a nucleating agent is an inorganic crystalline compound such as boron-containing compounds (e.g., boron nitride, sodium tetraborate, potassium tetraborate, calcium tetraborate, etc.), alkaline earth metal carbonates (e.g., calcium magnesium carbonate), oxides (e.g., titanium oxide, aluminum oxide, magnesium oxide, zinc oxide, antimony trioxide, etc.), silicates (e.g., talc, sodium aluminum silicate, calcium silicate, magnesium silicate, etc.), alkaline earth metal salts (e.g., calcium carbonate, calcium sulfate, etc.). Boron nitride (BN) has been found to be particularly beneficial when used in the polymer composition of the present invention. Boron nitride exists in a wide variety of crystalline forms (e.g., h-BN-hexagonal, c-BN-cubic or spharlerite, and w-BN-wurtzite), and generally any of these can be used in the present invention. The hexagonal form is particularly preferred due to its stability and softness.

[0053]

[0057] If desired, a crosslinking system can also be used in combination with any of the optional impact modifiers to help further improve the strength and flexibility of the composition under a variety of different conditions. In such a situation, a crosslinked product can be formed from a crosslinkable polymer composition containing a polyarylene sulfide together with one or more impact modifiers, a siloxane polymer, a filler, and a crosslinking system and other optional additives. The crosslinking system, which can contain one or more crosslinking agents, when used, typically accounts for about 0.1 to about 15 parts, in some embodiments about 0.2 to about 10 parts, in some embodiments about 0.5 to about 5 parts, per 100 parts of polyarylene sulfide, and about 0.05 wt% to about 15 wt%, in some embodiments about 0.1 wt% to about 10 wt%, in some embodiments about 0.2 wt% to about 5 wt% of the polymer composition. By using such a crosslinking system, the compatibility and distribution of the polyarylene sulfide and the impact modifier can be significantly improved. For example, the impact modifier can be dispersed in the polymer composition in the form of discrete domains of nanoscale size. For example, the domains can have an average cross-sectional dimension of about 1 to about 1000 nanometers, in some embodiments about 5 to about 800 nanometers, and in some embodiments about 10 to about 500 nanometers. The domains can have a variety of different shapes, such as ellipsoidal, spherical, cylindrical, plate-like, tubular, and the like. Such improved dispersion can result in better mechanical properties, or allow for the achievement of comparable mechanical properties with less impact modifier.

[0058] Any of a variety of different crosslinking agents can generally be used in the crosslinking system. In one embodiment, as an example, the crosslinking system may include a metal carboxylate. Without intending to be limited by theory, it is believed that the metal atom in the carboxylate may act as a Lewis acid to accept electrons from an oxygen atom located in the functional group (e.g., epoxy functional group) of the impact modifier. Upon reaction with the carboxylate, the functional group becomes activated and can be readily attacked at either carbon atom in the three-membered ring via a nucleophilic substitution reaction, thereby forming a crosslink between the chains of the impact modifier. The metal carboxylate is typically a metal salt of a fatty acid. The metal cation used in the salt may vary, but is typically a divalent metal such as calcium, magnesium, lead, barium, strontium, zinc, iron, cadmium, nickel, copper, tin, and the like, and mixtures thereof. Zinc is particularly preferred. The fatty acid may generally be any saturated or unsaturated acid with a carbon chain length of about 8 to 22 carbon atoms, and in some embodiments, about 10 to about 18 carbon atoms. Optionally, the acid may be substituted. Suitable fatty acids may include, for example, lauric acid, myristic acid, behenic acid, oleic acid, palmitic acid, stearic acid, ricinoleic acid, capric acid, neodecanoic acid, hydrogenated tallow fatty acid, hydroxystearic acid, hydrogenated castor oil fatty acid, erucic acid, coconut oil fatty acid, and the like, and mixtures thereof. The metal carboxylate typically comprises from about 0.05 wt% to about 5 wt%, in some embodiments from about 0.1 wt% to about 2 wt%, and in some embodiments from about 0.2 wt% to about 1 wt% of the polymer composition.

[0054]

[0059] Crosslinking systems can also use crosslinkers that are "multifunctional" to the extent that they contain at least two reactive functional groups. Such multifunctional crosslinkers can act as weak nucleophiles that can react with the activated functional groups (e.g., epoxy functional groups) of the impact modifier. The multifunctional nature of such molecules allows them to crosslink two functional groups of the impact modifier to effectively act as a curing agent. Multifunctional crosslinkers generally contain two or more reactively functional end moieties linked by bonds or non-polymeric (non-repeating) linking moieties. By way of example, crosslinkers can include diepoxides, multifunctional epoxides, diisocyanates, polyisocyanates, polyhydric alcohols, water-soluble carbodiimides, diamines, diols, diaminoalkanes, multifunctional carboxylic acids, diacid halides, and the like. Multifunctional carboxylic acids and amines are particularly suitable. Specific examples of polyfunctional carboxylic acid crosslinkers include, but are not limited to, isophthalic acid, terephthalic acid, phthalic acid, 1,2-di(p-carboxyphenyl)ethane, 4,4'-dicarboxydiphenyl ether, 4,4'-bisbenzoic acid, 1,4- or 1,5-naphthalenedicarboxylic acid, decahydronaphthalenedicarboxylic acid, norbornene dicarboxylic acid, bicyclooctane dicarboxylic acid, 1,4-cyclohexanedicarboxylic acid (both cis and trans), 1,4-hexylenedicarboxylic acid, adipic acid, azelaic acid, dicarboxydodecanoic acid, succinic acid, maleic acid, glutaric acid, suberic acid, azelaic acid, and sebacic acid. Corresponding dicarboxylic acid derivatives, such as carboxylic acid diesters, carboxylic acid anhydrides, or carboxylic acid halides having 1 to 4 carbon atoms in the alcohol group, may also be utilized. In certain embodiments, aromatic dicarboxylic acids, such as isophthalic acid or terephthalic acid, are particularly suitable.

[0055]

[0060] The multifunctional crosslinking agent, if used, typically comprises from about 50 wt% to about 95 wt%, in some embodiments from about 60 wt% to about 90 wt%, and in some embodiments from about 70 wt% to about 85 wt% of the crosslinked system, while the metal carboxylate typically comprises from about 5 wt% to about 50 wt%, in some embodiments from about 10 wt% to about 40 wt%, and in some embodiments from about 15 wt% to about 30 wt% of the crosslinked system. For example, the multifunctional crosslinking agent may comprise from about 0.1 wt% to about 10 wt%, in some embodiments from about 0.2 wt% to about 5 wt%, and in some embodiments from about 0.5 wt% to about 3 wt% of the polymer composition. Of course, in certain embodiments, the composition may generally be free of the multifunctional crosslinking agent, or the crosslinked system may generally be free of the metal carboxylate.

[0056]

[0061] Still other components that may be included in the composition can include, for example, particulate fillers (e.g., talc, mica, etc.), antimicrobial agents, pigments (e.g., black pigments), antioxidants, stabilizers, surfactants, waxes, flow promoters, solid solvents, flame retardants, and other materials added to enhance properties and processability.

[0057] II. Melt Processing

[0062] The method of combining the polyarylene sulfide and various additives can vary as known in the art. For example, the materials can be fed simultaneously or sequentially to a melt processing device that dispersively blends the materials. Batch and / or continuous melt processing techniques can be used. For example, mixers / kneaders, Banbury mixers, Farrel continuous mixers, single screw extruders, twin screw extruders, roll mills, etc. can be utilized to blend and melt process the materials. One particularly suitable melt processing device is a co-rotating twin screw extruder (e.g., Leistritz co-rotating fully intermeshed twin screw extruder). Such an extruder can include a feed section and a discharge section, providing a high intensity distribution and dispersion mixer. For example, the components can be fed to the same or different feed sections of a twin screw extruder and melt blended to form a substantially homogeneous molten mixture. The melt blending can occur under high shear / pressure and can be heated to ensure sufficient dispersion. For example, melt processing may occur at temperatures from about 100° C. to about 500° C., and in some embodiments, from about 150° C. to about 300° C. Similarly, the apparent shear rate during melt processing may be from about 100 s -1 ~about 10,000 seconds -1 , in some embodiments, about 500 seconds -1 ~Approx. 1,500 seconds -1 Of course, other variables such as residence time during melt processing, which is inversely proportional to throughput rate, can also be controlled to achieve the desired degree of uniformity.

[0058]

[0063] If desired, one or more distributive and / or dispersive mixing elements may be used within the mixing section of the melt processing unit. Suitable distributive mixers may include, for example, Saxon, Dulmage, Cavity Transfer mixers, and the like. Similarly, suitable dispersive mixers may include Blister ring, Leroy / Maddock, CRD mixers, and the like. As is well known in the art, the mixer may be further strengthened by using pins in the barrel that create folding and reorientation of the polymer melt, such as those used in Buss Kneader extruders, Cavity Transfer mixers, and Vortex Intermeshing Pin mixers. The screw speed may also be controlled to improve the properties of the composition. For example, the screw speed may be about 400 rpm or less, in one embodiment, for example, about 200 rpm to about 350 rpm, or about 225 rpm to about 325 rpm. In one embodiment, compounding conditions may be balanced to provide a polymer composition exhibiting improved properties. For example, compounding conditions may include a screw design that provides weak, medium, or strong screw conditions. For example, the system may have a weak strength screw design where the screw has a single melting section in the downstream half of the screw for gentle melting and distributive melt homogenization. A medium strength screw design may have a stronger melting section upstream of the filler feed barrel with more focused stronger dispersing elements for uniform melting. In addition, it may have another gentle mixing section downstream to mix the filler. This mixing section may be weaker than the weak strength design, but may be more powerful overall, adding to the shear strength of the screw. A highly strong screw design may have the strongest shear strength of the three. The main melting section may consist of a long array of highly dispersive kneading blocks. The downstream mixing section may utilize a mix of distributive and focused dispersing elements to achieve uniform dispersion of all fillers. The shear strength of the highly strong screw design may be significantly higher than the other two designs.In one embodiment, the system can include a medium to strong screw design with relatively moderate screw speeds (eg, about 200 rpm to about 300 rpm).

[0059]

[0064] The crystallization temperature of the resulting polymeric composition (before being formed into a molded part) may be about 250° C. or less, and in some embodiments, from about 100° C. to about 245° C., and in some embodiments, from about 150° C. to about 240° C. The melting temperature of the polymeric composition may also range from about 250° C. to about 320° C., and in some embodiments, from about 260° C. to about 300° C. Melting and crystallization temperatures may be determined as known in the art using differential scanning calorimetry according to ISO Test No. 11357-3:2018.

[0060] III. Components that are formed

[0065] A variety of different components can be formed using the polymer compositions described herein. Moreover, components can be formed from the polymer compositions using a variety of different techniques. Suitable techniques can include, for example, injection molding, low pressure injection molding, extrusion compression molding, gas injection molding, foam injection molding, low pressure gas injection molding, low pressure foam injection molding, gas extrusion compression molding, foam extrusion compression molding, extrusion molding, foam extrusion molding, compression molding, foam compression molding, gas compression molding, and the like. For example, an injection molding system can be used that includes a mold into which the polymer composition can be injected. The time in the injector can be controlled and optimized so that the polymer matrix is ​​not presolidified. Once the cycle time is reached and the barrel is full for discharge, the composition can be injected into the mold cavity using a piston. Compression molding systems can also be used. Similar to injection molding, shaping of the polymer composition into the desired article also occurs in the mold. The composition can be placed into the compression mold using any known technique, for example by lifting by an automated robotic arm. The temperature of the mold can be maintained above the solidification temperature of the polymer composition for the desired time to allow solidification. The molded article can then be solidified by lowering the temperature below the melting point. The resulting article can be demolded. The cycle time for each molding process can be adjusted to match the polymer composition to achieve sufficient bonding and enhance overall process productivity.

[0061] IV. Electric vehicles

[0066] As previously mentioned, the disclosed polymer compositions are particularly beneficial for use in components of electric vehicles. For example, referring to FIG. 1, one embodiment of an electric vehicle 112 is shown that includes a powertrain 110. The powertrain 110 includes one or more electric machines connected to a transmission 116 that is in turn mechanically connected to a drive shaft 120 and drive wheels 122. Although by no means required, the transmission 116 in this particular embodiment is also connected to an engine 118, however, the description herein is equally applicable to pure electric vehicles. The electric machine 114 can operate as a motor or generator to provide propulsion and deceleration capabilities. The powertrain 110 also includes a propulsion source, such as a battery assembly 124 that stores and provides energy for use by the electric machine 114. The battery assembly 124 typically provides high voltage current output (e.g., DC current at a voltage of about 400 volts to about 800 volts) from one or more battery cell arrays that may include one or more battery cells.

[0062]

[0067] The powertrain 110 may also contain at least one power electronics module 126, which is connected to a battery assembly 124 (also commonly referred to as a battery pack) and may contain a power converter (e.g., converter, etc., and combinations thereof). The power electronics module 126 is typically electrically connected to the electric machine 114 and provides the ability to transfer electrical energy bidirectionally between the battery assembly 124 and the electric machine 114. For example, the battery assembly 124 may apply a DC voltage, while the electric machine 114 may require a three-phase AC voltage to function. The power electronics module 126 may convert the DC voltage to a three-phase AC voltage as required by the electric machine 114. In a regeneration mode, the power electronics module 126 may convert the three-phase AC voltage from the electric machine 114 acting as a generator to the DC voltage required by the battery assembly 124. The battery assembly 124 may also provide energy for other vehicle electrical systems. For example, the powertrain may use a DC / DC converter to convert high voltage DC power generated from the battery assembly 124 to a low voltage DC supply compatible with other vehicle loads, such as a compressor and electric heater. In a typical vehicle, the low voltage system is electrically connected to an auxiliary battery 130 (e.g., a 12V battery). There may also be a battery energy control module (BECM) 133 in communication with the battery assembly 124, which acts as a controller for the battery assembly 124 and may include an electronic monitoring system that manages the temperature and charge state of each battery cell. The battery assembly 124 may also have a temperature sensor 131, such as a thermistor or other thermometer. The temperature sensor 131 may be in communication with the BECM 133 to provide temperature data regarding the battery assembly 124. The temperature sensor 131 may be located on or near a battery cell within the traction battery 124. It is also contemplated that multiple temperature sensors 131 may be used to monitor the temperature of the battery cells.

[0063]

[0068] In certain embodiments, the battery assembly 124 may be recharged by an external power source 136, such as an electrical outlet. The external power source 136 may be electrically connected to an electric vehicle supply equipment (EVSE), which regulates and manages the transfer of electrical energy between the power source 36 and the vehicle 112. The EVSE 138 may have a charging connector 140 for plugging into a charging port 134 of the vehicle 112. The charging port 134 may be any type of port configured to transfer power from the EVSE 138 to the vehicle 112 and may be electrically connected to a charger or onboard power conversion module 132. The power conversion module 132 may condition the power provided by the EVSE 138 and provide the appropriate voltage and current levels to the battery assembly 124. The power conversion module 132 may interface with the EVSE 138 to coordinate the delivery of power to the vehicle 112.

[0064]

[0069] The polymer compositions described herein may be included in various components of the electric vehicle shown in FIG. 1. As an example, bus bars (one example is shown in FIG. 2) may be used to electrically connect the individual cells of the battery assembly 124. With reference to FIG. 3, for example, the battery assembly 124 may include a number of battery cells 158. The battery cells 158 may be stacked in parallel to construct a grouped battery cell (sometimes referred to as a battery array). In one embodiment, the battery cells 158 are prismatic lithium-ion batteries. However, battery cells having other shapes (cylindrical, pouch, etc.) and / or chemistries (nickel-metal hydride, lead-acid, etc.) may alternatively be utilized within the scope of the present disclosure. Each battery cell 158 includes a positive terminal (denoted with a (+) symbol) and a negative terminal (denoted with a (-) symbol). The battery cells 158 are arranged such that the terminal of each battery cell 158 is disposed adjacent to the terminal of an adjacent battery cell 158 having an opposite polarity. As used herein, the terms "battery," "cell," and "battery cell" may be used interchangeably and may refer to any type of individual battery element used in a battery system. The batteries described herein typically include lithium-based batteries, but may also include a variety of chemistries and configurations, including iron phosphate, metal oxide, lithium ion polymer, nickel metal hydride, nickel cadmium, nickel-based batteries (hydrogen, zinc, cadmium, etc.), and any other battery type compatible with electric vehicles. For example, some embodiments may use a Panasonic® 6831NCR18650 battery cell, or some variation of the 18650 form factor that is 6.5 cm by 1.8 cm and approximately 45 g.

[0065]

[0070] The manner in which the busbar connects to the individual battery cells of a battery assembly 124, as shown in FIG. 3, can vary as known in the art. Referring to FIG. 2, one embodiment of a busbar 10 is shown, which includes electrical conductors 12. The electrical conductors 12 include a conductive material 18, such as copper, aluminum, an aluminum alloy, and may generally be in the form of a solid bar, a hollow tube, and the like. The busbar 10 includes a connector portion 14 at either end configured to mate with each terminal of two or more batteries. An insulating portion 16 (e.g., a coating or molding compound) including a polymer composition described herein may cover a portion of the conductive material of the electrical conductors 12. To form the busbar 10, the insulating portion 16 may be applied to a surface of the conductive material 18. As an example, the busbar 10 can be shaped into any suitable form after a bar or tube of the conductive material 18 is inserted into a preformed tube of insulating coating 16 (e.g., an extruded tube sized and cut to precise proportions). In another embodiment, an insulating coating may be applied to the surface of the conductive material 18 in the melt and allowed to solidify on the surface of the conductive material where applied.

[0066]

[0071] Of course, the busbars may be provided in any suitable shape and size. As an example, the busbars may be used as a template for uniformly positioning the individual battery cells in each battery assembly produced. In such an embodiment, the busbars may hold the individual batteries of the battery assembly 124 in place during the manufacturing process, allowing thermal padding or injection housing, which may be formed from the polymer compositions described herein, to be added without displacing the individual battery cells.

[0067]

[0072] Apart from bus bars, other components may also use the polymer composition of the present invention. As an example, FIG. 4 depicts a block diagram of battery electronics of an electric vehicle 112. The illustrated battery electronics system includes a battery assembly 124 and a current sensor 142. As shown, the current sensor 142 is connected between the battery assembly 124 and a load / source 144. The current sensor 142 may be configured to measure a current flowing from the battery assembly 124 to the load / source 144 when the load / source 144 is a load, such as one or more electric machines 114. Similarly, the current sensor 142 may be configured to measure a current flowing from the load / source 144 to the battery assembly 124 when the load / source 144 is a source, such as an external power source 136. The (BECM) 133 may be configured to enable operation of the current sensor 142. Additionally, the BECM 133 may be configured to read an output generated by the current sensor 142 indicative of a current flowing between the battery assembly 124 and the load / source 144.

[0068]

[0073] 5 illustrates one embodiment of a current sensor 142. The current sensor 142 may include a current input terminal 141 and a current output terminal 143 as well as a reference ground 145, a voltage at common collector (VCC) 146, and an output port 147. The current sensor 142 may also include a housing 148 comprising a described polymer composition that may house other components of the current sensor 142 (e.g., resistors, capacitors, converters, processing chips, etc.).

[0069]

[0074] Another component of an electric vehicle in which the described polymer composition can be incorporated is an inverter system, an exemplary embodiment of which is shown in FIG. 6. The system includes an inverter module 320 and an interconnect system 335. The interconnect system 335 includes an electromagnetic interference (EMI) core 330 and an EMI filter device 325. The inverter module 320 is coupled to the interconnect system 335 by a pair of bus bars 310. The EMI core 330 is located between the EMI filter device 325 and the inverter module 320 and is in communication with the bus bars 310. The EMI filter device 325 includes an EMI filter card 340 and a pair of bolts 350 and 352 including a positive terminal (+) bolt 350 and a negative terminal (-) bolt 352 for coupling to a power source, such as the battery assembly 124. The EMI core 330 is coupled to the bolts 350 and 352 by the bus bars 310. The EMI filter card 340 is also coupled between ground and the bus bars 310 via a pair of wires 334. The inverter module 320 includes a large number of transistors (not shown). The transistors in the inverter module 320 switch relatively quickly (e.g., 5-20 kHz). This switching tends to generate electrical switching noise. The electrical switching noise should ideally be contained within the inverter module 320 and prevented from entering other electrical systems to prevent interference with other electrical components in the vehicle.

[0070]

[0075] The inverter system may include several components into which the disclosed polymer compositions may be incorporated, such as, but not limited to, the EMI filter device 325 (e.g., as a housing and / or internal support structure), the EMI filter card 340, the busbar 310, and connectors used within the system. For example, an electrical connector including the polymer compositions described herein may be used in the inverter system of FIG. 7 or in another portion of the electric vehicle. The electrical connector may generally include a first connector portion containing at least one electrical contact and an insulating member surrounding at least a portion of the connector portion. The insulating member may include the polymer composition of the present invention. The first connector portion may be configured to mate with an opposing second connector portion containing a receptacle for receiving the electrical contact. In such an embodiment, the second connector portion may include at least one receptacle configured to receive the electrical contact of the first connector portion and an insulating member surrounding at least a portion of the second connector portion. The insulating member of the second connector portion may also include the polymer composition of the present invention.

[0071]

[0076] 7, 8, and 9, one particular embodiment of a connector 200 for use in an electric vehicle, such as an electric vehicle powertrain, is shown. The connector 200 includes a first connector portion 202 and a second connector portion 204. The first connector portion 202 may include one or more electrical pins 206, and the second connector portion 204 may include one or more receptacles 208 for receiving the electrical pins 206. A first insulating member 212 may extend from a bottom surface 203 of the first connector portion 202 to surround the pins 206, and similarly, a second insulating member 218 may extend from a bottom surface 201 of the second connector portion 204 to surround the receptacles 208. In certain cases, a side of the first insulating member 212 may extend beyond an end 203 of the electrical pins, and a side of the second insulating member 218 may extend beyond an end of the receptacle 208. The bottom surface 203 and / or the first insulating member 212 of the first connector portion 202, and the bottom surface 201 and / or the second insulating member 218 of the second connector portion 204 may be formed from a polymer composition of the present invention.

[0072]

[0077] Although by no means required, first connector portion 202 may also include an identification mark 210 secured to or defined by first protective member 212. Second connector portion 204 may also optionally define an alignment window 220 sized by identification mark 210 to more easily determine when the connector portions are fully mated. By way of example, identification mark 210 cannot be read unless blocking portion 221 covers a portion of identification mark 210. Optionally, second connector portion 204 may include a preliminary mark 224 located adjacent alignment window 220.

[0073]

[0078] Figures 10 and 11 show still other examples of components in which the polymer compositions of the present invention can be used (such as spacers, connectors, insulators and supports as shown in Figure 10) and components that can be formed from the polymer compositions. Components shown in Figure 11 into which the polymer compositions can be incorporated include quick connectors, tees, and interconnects (several are shown at the top of Figure 11); brushless DC motors (center left of Figure 11), such as motor sealing rings, housings, supports, etc.; guide rails (center right of Figure 11, with an additional example of a bus bar also shown in the image); and battery sealing rings (bottom of Figure 11).

[0074]

[0079] The systems that can use the polymer composition of the present invention are by no means limited to electrical systems. For example, thermal management systems can also beneficially incorporate the polymer composition. The thermal management system of an electric vehicle can generally include a number of different subsystems, such as, but not limited to, a powertrain subsystem, a cooling subsystem, a battery cooling subsystem, and a heating, ventilation, and air conditioning (HVAC) subsystem. In some embodiments, one or more subsystems of the thermal management system can be fluidly connected to each other, thus allowing a high temperature heat transfer medium to flow from a high temperature circuit to a low temperature circuit, and allowing a lower temperature heat transfer medium to flow from the low temperature circuit to the high temperature circuit.

[0075]

[0080] For example, FIG. 12 shows a first temperature control loop and FIG. 13 shows a second temperature control loop, each of which is found in an electric vehicle, each designed for a different subsystem, each of which includes one or more components that can use the polymer composition of the present invention. For example, the first temperature control loop of a typical electric vehicle (FIG. 12) can include a heat transfer medium (e.g., water) that is pumped through the loop via a suitable pump 160 (e.g., an electric water pump) and cooled via heat transfer with a coolant in a heat exchanger 162 (e.g., an energy storage system (ESS) heat exchanger) as well as a radiator / reservoir 164. In addition, the loop can include a heater 166 (e.g., a positive temperature coefficient (PTC) heater) that can ensure that the temperature of the system can be maintained within a preferred operating range regardless of the ambient temperature, and the battery assembly 124. The second temperature control loop (FIG. 13) can also include a heat transfer medium that can be the same or different from the heat transfer medium of another subsystem. The heat transfer medium of the second temperature control loop may be pumped through a loop with a suitable pump 161, heat exchanger 162, and radiator reservoir 165. The high temperature control loop may be utilized for cooling the power electronics 167 and the electric machine 114 of the vehicle.

[0076]

[0081] One example of a component of a thermal management system that may incorporate the polymer composition of the present invention is a coolant pump, such as an electric water pump, an example of which is shown in FIG. 14. As shown, the electric water pump 401 includes an electric motor 410 as a driving source and a hydraulic section 420 that generates coolant suction and discharge forces. The motor 410 and associated components are held within a motor housing 411. The hydraulic section 420 generally includes a volute casing 421 that includes a helical flow space, an inlet 422, and an outlet 423, and an impeller (not shown) that is rotated by the electric motor 410. The pump 401 has an interface that includes a mechanical seal (not shown) for sealing and separating the water flow space and the motor chamber. Typically, a mounting section 412 is provided on the motor housing 411 for mounting the pump 401 within a vehicle. The components of the electric pump 401, such as the housing, casing, interfaces, etc., may incorporate the polymer composition of the present invention.

[0077]

[0082] The invention may be better understood with reference to the following examples. EXAMPLES

[0078] Test Method

[0083] Melt viscosity: Melt viscosity (Pa s) is measured at a shear rate of 400 s according to ISO11443:2021. -1 The melt viscosity may be determined using a Dynisco LCR7001 capillary rheometer at 300° C. The rheometer orifice (die) may have a diameter of 1 mm, a length of 20 mm, an L / D ratio of 20.1, and an entry angle of 180°. The barrel diameter may be 9.55 mm+0.005 mm and the rod length was 233.4 mm. Melt viscosity is typically determined at a temperature of 310° C.

[0079]

[0084] Tensile modulus, tensile stress at break, and tensile strain at break: Tensile properties may be tested according to ISO527-2 / 1A:2019 (technically equivalent to ASTM D638-14). Modulus and strength measurements may be performed on the same test piece sample with a length of 80 mm, a thickness of 10 mm, and a width of 4 mm. The test temperature may be 23°C, and the test speed may be 5 mm / min for tensile strength and tensile strain at break, and 1 mm / min for tensile modulus.

[0080]

[0085] The notched Izod impact strength can be determined according to ISO 180:2019. The test specimens were cut from the center of the multipurpose bar using a single-tooth milling machine. The test temperature was 23°C.

[0081]

[0086] Notched Charpy Impact Strength: Charpy properties may be tested according to ISO test number ISO 179-1:2010 (technically equivalent to ASTM D256-10, Method B). This test may be performed using Type 1 specimen dimensions (length 80 mm, width 10 mm, and thickness 4 mm). When testing notched impact strength, the notch may be a Type A notch (base radius 0.25 mm). The specimen may be cut from the center of the multipurpose bar using a single tooth milling machine. The test temperature may be 23°C or -30°C.

[0082] Examples 1-2

[0087] Examples 1-2 were melt mixed using a Coperion 32mm co-rotating, fully intermeshed twin screw extruder and contained various concentrations of polyarylene sulfide, impact modifier, glass fiber, siloxane polymer, organosilane, and coolant. The impact modifier was a random copolymer of ethylene and glycidyl methacrylate with 8 wt% glycidyl methacrylate content and a melt flow index of 5 g / 10 min at 190°C. The siloxane polymer was a UHMW functionalized siloxane polymer provided as a masterbatch with 50% siloxane content and 50% resin content. The organosilane was 3-aminopropyltriethoxysilane. The formulations for each example are detailed in the table below.

[0083] [Table 2]

[0084]

[0088] After formation, the samples were tested for various physical properties and the results are set forth below.

[0085] [Table 3]

[0086]

[0089] Example 1 was reformulated (Example 1a) and retested for various physical properties before and after heat aging at 240° C. for 1000 hours.

[0087] [Table 4]

[0088]

[0090] These and other modifications and variations of the present invention may be practiced by those skilled in the art without departing from the spirit and scope of the present invention. In addition, it should be understood that aspects of the various embodiments may be interchanged both in whole or in part. Furthermore, those skilled in the art will appreciate that the foregoing description is by way of example only and is not intended to limit the invention as further described in the appended claims.

Claims

1. 100 parts by weight of at least one polyarylene sulfide; about 10 to about 80 parts by weight of a fibrous filler; from about 1 to about 20 parts by weight of at least one impact modifier; from about 0.1 to about 10 parts by weight of an ultra-high molecular weight siloxane polymer having a weight average molecular weight of about 100,000 grams / mole or greater; 1. A polymer composition comprising:

2. The polymer composition of claim 1 , wherein the siloxane polymer is functionalized.

3. 3. The polymer composition of claim 2, wherein the siloxane polymer comprises one or more of vinyl, hydroxyl, hydride, isocyanate, epoxy, acid, halogen, alkoxy, acyloxy, ketoximate, amino, amide, acid amide, aminooxy, mercapto, alkenyloxy, alkoxyalkoxy, or aminoxy groups.

4. 10. The polymer composition of claim 1, further comprising about 0.1 to about 8 parts by weight of an organosilane compound.

5. The polymer composition of claim 4 , wherein the organosilane compound comprises an aminoalkoxysilane.

6. The polymer composition of claim 1 , wherein the fibrous filler comprises glass fibers.

7. The polymer composition of claim 1 , wherein the impact modifier comprises an epoxy-functionalized monomer unit.

8. 8. The polymer composition of claim 7, wherein the epoxy-functionalized monomeric unit comprises an epoxy-functionalized (meth)acrylic monomer component.

9. 9. The polymer composition of claim 8, wherein the epoxy-functionalized (meth)acrylic monomer component is formed from glycidyl acrylate, glycidyl methacrylate, or a combination thereof.

10. The polymer composition of claim 7, wherein the impact modifier further comprises an α-olefin monomer component.

11. 11. The polymer composition of claim 10, wherein the α-olefin monomer component comprises from about 55 wt % to about 95 wt % of the impact modifier and the epoxy-functionalized (meth)acrylic monomer component comprises from about 1 wt % to about 20 wt % of the impact modifier.

12. 12. The polymer composition of claim 11, wherein the impact modifier further comprises a non-epoxy functionalized (meth)acrylic monomer component in an amount of about 5 wt% to about 35 wt% of the polymer.

13. 10. The polymer composition of claim 1, wherein the impact modifier has a melt flow index of about 1 to about 30 grams per 10 minutes as determined according to ASTM D1238-13 at a load of 2.16 kg and a temperature of 190°C.

14. The polymer composition of claim 1 , wherein the polyarylene sulfide comprises from about 50 wt % to about 98 wt % of the polymer composition.

15. The polymer composition of claim 1 , wherein the polyarylene sulfide is polyphenylene sulfide.

16. 16. The polymer composition of claim 15, wherein the polyarylene sulfide is a linear polyphenylene sulfide.

17. The polymer composition has a thermal conductivity of about 5 kJ / m when determined at 23° C. according to ISO 180:2019 2 2. The polymer composition of claim 1, exhibiting a notched Izod impact strength of or greater.

18. 10. The polymer composition of claim 1, wherein the polymer composition exhibits a tensile strength of greater than or equal to about 100 MPa, as determined according to ISO 527:2019 at a temperature of 23°C.

19. The polymer composition is subjected to a shear rate of 400 s at a temperature of about 310° C. according to ISO 11443:2021. -1 2. The polymer composition of claim 1, exhibiting a melt viscosity of about 30 kP or less, as determined by

20. 13. An electric vehicle comprising a powertrain including at least one electric propulsion source and a transmission connected to the propulsion source through at least one power electronics module, the electric vehicle comprising the polymer composition of claim 1.

21. 21. The electric vehicle of claim 20, wherein the electric vehicle includes an electrical component comprising the polymer composition.

22. 22. The electric vehicle of claim 21, wherein the electrical components include bus bars, current sensors, inverter filters, electrical connectors, brushless DC motors, guide rings, battery cell sealing rings, or combinations thereof.

23. 22. The electric vehicle of claim 21, wherein the electrical component comprises a quick connector, a tee, an interconnector, or a combination thereof.

24. 21. The electric vehicle of claim 20, wherein the electric vehicle includes a thermal management system component that includes the polymer composition.

25. 25. The electric vehicle of claim 24, wherein the thermal management system component includes a coolant pump.